Results of metastatic liver irradiation - Słomian, Grzegorz; Woźniak, Grzegorz; Miszczyk, Leszek (Contemporary Oncology/Współczesna Onkologia, 2002)
The group of 50 patients with multiple hepatic metastases who underwent palliative liver irradiation was analysed. The age ranged from 31 to 76 years (mean 57). In 35 cases the primary tumour was located in digestive tract and in 15 in other places. In 28 cases colon cancers were origins of metastases. There were 48 carcinomas and 2 sarcomas. In 36 cases adenocarcinoma was found. Majority of patients were in good performance status (65% Zubrod 0-1, 35% Zubrod 2). In 60% of patients more than ten liver metastases were found. The mean metastases diameter was 4,7 cm. 15 patients had metastases in other organs and 18 bulky, primary tumour. In 29 cases the liver volume increase was found. 27 patients were previously treated with chemotherapy (mainly 5-Fluorouracyl and leucovorin), 4 with hormono and 1 with immunotherapy. The liver function as by biochemical examination was proper in majority of cases (mean ASPAT, ALAT, alkalic phosphatase and bilirubin levels were respectively 37 iu, 33 iu, 214 iu and 20.4 mmol/l). 60% of patients suffered from pain in liver region. The majority of patients were irradiated with fraction dose of 1.8 Gy to the total dose of 18 Gy in average time of 14 days. 39 patient were irradiated using gamma 60 Co, 10 with high energy photons and 1 with orthovoltage x-rays. The mean follow up was 4.1 months. The aim of the study was to assess adverse effects of such treatment and its effectiveness. In no one case the treatment was interrupted because of a radiation morbidity. The only toxicity was temporary nausea treated with metoclopramid and thiethylperazini. One month after treatment completion 32% of patients reported complete pain relief in the comparison to a level before the treatment. In following monthly examinations, the percentage of such patients was 23%, 29% and 10%. Only particular patients reported analgetics intake. The number of patients in following controls gradually decreased but the performance status and liver function of controlled patients were stable. The obtained results allow to form the conclusion that radiotherapy of metastatic liver is easy and effective palliative treatment modality allowing to obtain comparable to other methods result and being well tolerated by disseminated cancer patients.